Laparoscopic cholecystectomy: An experience at College of Medical Sciences, Teaching Hospital, Bharatpur Nepal - Kumar, S; Patowary, BN; Hirachan, S; Shrestha, P (Journal of College of Medical Sciences-Nepal, 2012)
Laparoscopic cholecystectomy is the "gold standard" for benign gallbladder diseases. Laparoscopic cholecystectomy has rapidly gained popularity and it is one of the commonly performed operations in Nepal. Laparoscopic Cholecystectomy first performed by Muhe in 1985. The current descriptive study is carried out in Department of General Surgery, College of Medical Sciences – Teaching Hospital (CMS-TH), Bharatpur to evaluate the result of Laparoscopic Cholecystectomy in symptomatic gallstones disease in our set up with special emphasis on complication rate, morbidity and mortality. The data of all patients who underwent laparoscopic cholecystectomy form March 2008 to March 2009 was entered in standardized proforma and analysed on SPSS 10. Out of 110 patients, 85 (77.27%) were female and 25 (22.73%) were males; the age range from 17 to 70 years mean age being 41.30 years, majority were in age 25–40 years group. Eight (7.2%) patients had bile leak, 2 (1.8%) patients developed port site wound infection. There was no bile duct or colonic injuries. The conversion rate was 7.2% (in 8 patients). There was no mortality. Journal of College of Medical Sciences-Nepal, 2011, Vol-7, No-3, 6-10 DOI: http://dx.doi.org/10.3126/jcmsn.v7i3.6701